Indipendenza e professionalità del giudice in Cina - Mugelli, Caterina (Premio Tesi di Dottorato, 2012)
Corollary of the doctrine of the separation of powers and pillar of the rule of law, the principle of the independence of the judiciary is of great importance, especially in the Western legal tradition. Her analysis, focused on China, cannot be separated from an understanding of the reality in which it must be applied, from the knowledge of the legal class, the relations between the powers of the state and the history of the Communist Party. The purpose of this work is therefore to define the independence and professionalism of the Chinese judge at a regulatory level, framing the two concepts in a historical context and with comparisons with Western dynamics in order to recover the ultimate purpose of the judicial function: the impartiality of the decision.